A phase I trial adding poly(ADP-ribose) polymerase inhibitor veliparib to induction carboplatin-paclitaxel in patients with head and neck squamous cell carcinoma: Alliance A091101. (March 2021) - Jelinek, Michael J.; Foster, Nathan R.; Zoroufy, Alex J.; Schwartz, Gary K.; Munster, Pamela N.; Seiwert, Tanguy Y.; de Souza, Jonas A.; Vokes, Everett E.
Highlights: Adding veliparib to induction chemotherapy was well tolerated in head/neck cancer. Hematologic toxicities were most common when combining veliparib and chemotherapy. Adding veliparib to induction chemotherapy did not delay time to curative treatment. Abstract: Objectives: We report the results of this phase I study to evaluate the maximum tolerated dose (MTD) and safety of veliparib, a poly(ADP-ribose) polymerase (PARP) inhibitor, combined with carboplatin and paclitaxel induction chemotherapy (IC) for locoregionally advanced head and neck squamous cell carcinoma (HNSCC). Materials and methods: In a 3 + 3 cohort design, patients with stage IVA-B human papillomavirus-negative HNSCC received 2 cycles of carboplatin (AUC 6, day 1), paclitaxel (100 mg/m 2, days 1, 8, 15) and veliparib (days 1–7) every 21 days followed by standard curative-intent chemoradiotherapy. Primary endpoint: MTD and recommended phase II dose (RP2D) as determined by the first IC cycle. Results: Twenty patients enrolled. Two withdrew before treatment; 18 patients were analyzed. Median age was 63 years. Primary disease sites included hypopharynx (n = 5), larynx (n = 5), oral cavity (n = 4), oropharynx (n = 3), and nasal cavity (n = 1). Through all of IC, the most common grade 3 + adverse events (AEs) were neutropenia (33%), thrombocytopenia (33%), anemia (11%), and white blood cell decrease (11%). One patient experienced a hematologic DLT at 350 mg BID. The RP2D for veliparib combined with carboplatin/paclitaxel is 350 mg BID. With 40.9 month median follow-up across dose levels for all patients, the 24-month overall and progression free survival was 77.8% (95% CI 60.8–99.6%) and 66.7% (95% CI 48.1–92.4%), respectively. Medians have not been reached. Conclusion: Addition of veliparib to carboplatin and paclitaxel IC was well tolerated in patients with advanced HNSCC. Hematologic toxicities were the most common AEs.